PROGRAM HOLISTIK PEMBANGUNAN PEMBERDAYAAN DESA (PHP2D) OPTIMALISASI BALAI BANJAR SEBAGAI RUMAH BELAJAR PADA MASA COVID 19 DI DESA CEPAKA TABANAN - Ni Luh Putu Agustini Karta; I Ketut Sutapa; Rani Kusumo Wardani; Erna Wiles (Synergy and Society Service, 2021)
The Covid 19 pandemic has weakened the economy of the world community. The resulting impact is felt by all levels of rural and urban society; among parents, adults and children. Amid the economic downturn, people must survive. Various alternative efforts were made so that people could still eat and receive education. Especially school children who are very risky if their education is stopped for a relatively long time. This condition motivates the HIMA Accounting and Management of Triatma Mulya University to implement the PHP2D program through the optimization of the Banjar Hall as a Learning Center in the Covid 19 Pandemic Era in Cepaka Village, Tabanan, Bali. used as an arena for monthly meetings. Through this PHP2D program, the Banjar Hall is now equipped with internet facilities, work desks and bookshelves for libraries. Every day at 15-18 wita the children in each banjar; come to study with the help of students and lecturers. The availability of free internet and the presence of 5 students as teachers / mentors in each banjar make a positive contribution to the community and children in Cepaka village. After four months of this activity, a very harmonious relationship was formed between students and school children ranging from elementary and junior high schools. School children, totaling nearly 150 children, are trained in their learning, academic, soft skills and hard skills in order to grow into a superior generation. This activity received a warm welcome from the community, even the Head of Kediri Sub-district was very grateful and made Cepaka Village the first project pilot village to provide a learning house with free wi-fi. It is hoped that in the next period other villages can also be developed, students help children in learning so that they can achieve their goals.